Statistical evaluation of laminate configuration effects on hybrid composite structural behavior - Achmad Jusuf Zulfikar; Siswo Pranoto; Mulia; Derlini; Zakir Husin (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2026)
The growing demand for sustainable yet high-performance structural materials has accelerated research into hybrid composite systems that combine natural and synthetic fiber reinforcements. Hybrid jute/E-glass/epoxy laminates offer a promising balance between environmental sustainability and mechanical reliability; however, their structural behavior is strongly influenced by laminate configuration. This study aims to statistically evaluate the effects of stacking sequence on the structural performance of hybrid composites, focusing on three primary objectives: (i) experimentally assessing flexural and splitting tensile behavior under controlled loading conditions, (ii) determining the statistical significance of laminate configuration using Analysis of Variance (ANOVA), and (iii) investigating the relationship between mechanical strength enhancement and crack pattern development. The experimental program involved the fabrication of multiple laminate configurations using vacuum-assisted processing, followed by three-point bending and splitting tensile tests in accordance with standardized procedures. Crack patterns were quantified through digital image analysis to determine the percentage of damaged surface area. The results demonstrate that alternating stacking sequences significantly improve load-bearing capacity compared to non-optimized configurations. ANOVA confirmed that laminate arrangement exerts a statistically significant effect on mechanical performance. Furthermore, a meaningful correlation was observed between increased tensile strength and greater post-failure crack surface percentage, indicating a trade-off between structural resistance and damage manifestation. These findings provide a statistically validated framework for optimizing hybrid laminate configurations in sustainable structural applications and contribute to the advancement of performance-based composite design strategies.